PENGARUH JARAK ANODA-KATODA TERHADAP BERAT LAPISAN HASIL ELEKTROPLATING NIKEL PADA ALUMUNIUM ALLOY SERI 7075-T6 - Dedy Dwi Setiawan; Ferry Setiawan; Sehono (Journal of Applied Mechanical Engineering and Renewable Energy, 2022)
Electroplating serves to protect surfaces that make objects made of metal-containing materials more resistant to corrosion, make objects shiny, and make metals stronger. This research was conducted in order to determine the effect of the anode-cathode distance on the weight of the coating produced in the electroplating process. In this study, a test will be carried out using the electroplating method to determine the effect of the distance from the anode and cathode on the weight of the nickel layer coated on the 7075 aluminum alloy. of 3 grams, and the smallest result at the anode-cathode distance with a distance of 30 cm with a layer weight result of 1 gram. Based on the results of the data obtained, it can be concluded that the distance greatly affects the weight of the coating where the closer the anode-cathode distance is, the greater the layer weight, and if the anode-cathode distance is further away, the layer weight will be smaller.